Myelin sheath injury and repairment after subarachnoid hemorrhage - Chen, Mao; Guo, Peiwen; Ru, Xufang; Chen, Yujie; Zuo, Shilun; Feng, Hua (Frontiers in Pharmacology, 2023)
Subarachnoid hemorrhage (SAH) can lead to damage to the myelin sheath in white matter. Through classification and analysis of relevant research results, the discussion in this paper provides a deeper understanding of the spatiotemporal change characteristics, pathophysiological mechanisms and treatment strategies of myelin sheath injury after SAH. The research progress for this condition was also systematically reviewed and compared related to myelin sheath in other fields. Serious deficiencies were identified in the research on myelin sheath injury and treatment after SAH. It is necessary to focus on the overall situation and actively explore different treatment methods based on the spatiotemporal changes in the characteristics of the myelin sheath, as well as the initiation, intersection and common action point of the pathophysiological mechanism, to finally achieve accurate treatment. We hope that this article can help researchers in this field to further clarify the challenges and opportunities in the current research on myelin sheath injury and treatment after SAH.